2010
DOI: 10.1111/j.1472-765x.2010.02909.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of agitation and aeration on the production of nitrile hydratase by Rhodococcus erythropolis MTCC 1526 in a stirred tank reactor

Abstract: Aims:  To evaluate the effect of different physicochemical parameters such as agitation, aeration and pH on the growth and nitrile hydratase production by Rhodococcus erythropolis MTCC 1526 in a stirred tank reactor. Methods and Results:  Rhodococcus erythropolis MTCC 1526 was grown in 7‐l reactor at different agitation, aeration and controlled pH. The optimum conditions for batch cultivation in the reactor were an agitation rate of 200 rev min−1, aeration 0·5 v/v/m at controlled pH 8. In this condition, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Kinetic analysis indicated that cell accumulation and MCA productivity were enhanced during the first 16 h at a K L a of 72.2 h -1 . It has been reported that sufficient oxygen supply is necessary for the synthesis of enzymes, nucleic acids, vitamins and other essential metabolites [22,23]. Therefore, higher availability of dissolved oxygen is favorable for high cell density accumulation and ultimately a high MCE yield.…”
Section: Discussionmentioning
confidence: 99%
“…Kinetic analysis indicated that cell accumulation and MCA productivity were enhanced during the first 16 h at a K L a of 72.2 h -1 . It has been reported that sufficient oxygen supply is necessary for the synthesis of enzymes, nucleic acids, vitamins and other essential metabolites [22,23]. Therefore, higher availability of dissolved oxygen is favorable for high cell density accumulation and ultimately a high MCE yield.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress caused by excess oxygen and other oxides limits the growth of aerobic [33]. Oxidative and high-shear damage on R. erythropolis was also observed by Kamble and Meena [32] while increasing agitation speed from 200 to 300 rpm.…”
Section: Box-behnken Optimization Of Growth Conditionsmentioning
confidence: 68%
“…Rhodococcus erythropolis is known to be a flocculating agent for bioremediation processes [31]. However, flocculating activity of this organism negatively affects the growth rate by forming cell floccules and biofilms, reducing efficiency of aeration and agitation [32]. Furthermore, as the agitation speed was further increased, limitation in growth was observed.…”
Section: Box-behnken Optimization Of Growth Conditionsmentioning
confidence: 98%
“…Agitation rate is known to affect growth and enzyme production of some nitrilase producing bacteria [23]. Recombinant microorganisms can be particularly sensitive to the agitation regimen in a bioreactor [24].…”
Section: Effect Of Agitationmentioning
confidence: 99%
“…Oxygen is vital for the growth of the aerobic organism, however, at higher aeration rate, enzyme activity may be adversely affected. This fermentation therefore required a relatively high oxygen transfer capability in the bioreactor, but not an excessively intense hydrodynamic shear environment [23].…”
Section: Effect Of Aerationmentioning
confidence: 99%